The macroeconomic and fiscal impact of population ageing - Katalin Bodnár; Carolin Nerlich (European Central Bank (ECB), 2022)
The euro area, like many other advanced economies, has entered an era of drastic demographic change. Without appropriate policy responses, population ageing in the euro area is posing formidable challenges for potential growth, monetary policy and public finances. This paper examines - from a central bank's perspective - the macroeconomic and fiscal effects of population ageing in the euro area and looks at the main challenges ahead in the next decades. Total population in the euro area is projected to decline as of around 2035, while the old-age dependency ratio will rise strongly in the coming 15 years, putting additional burden on pension systems. The analysis in the paper finds that the demographic changes in the euro area present a drag on potential growth, mainly through labour supply and productivity growth - similarly to developments in Japan, which is ahead of the euro area in terms of population ageing. Precautionary savings may be higher, and the natural rate of interest lower, while the effect on trend inflation and wages are not obvious. Population ageing is posing a burden on fiscal policy, through upward pressure on pension spending and adversely affecting the tax bases and the structure of public revenues. Thus, it poses significant challenges for fiscal sustainability, limits fiscal policy space and effectiveness. To safeguard against the adverse economic and fiscal consequences of population ageing, there is a need for fiscal buffers, improved quality of public finance and structural reforms.
Keywords: E24; E52; E62; J11; J21; 330; population ageing; fiscal policy; potential growth; labour force; euro area; Japan